Perception of non-accounting students in UiTM Negeri Sembilan on Accounting Information Systems course - Hussin, Amariah Hanum; Muda, Salwa; Mohamed Sadique, Raziah Bi; Abdul Halim, Siti Mariam; Musman, Musliha (2022)
In this new technological era, knowledge in multidisciplinary courses will provide students with opportunities to learn beyond their main course. Understanding the core course thoroughly is crucial. Enrolling students in other courses will provide them with broader perspectives and experience, boosting their capacity to combine skill sets and expertise and resulting in immediate future career success. AIS615 is an accounting information system course offered to non-accounting students from the Faculty of Computer and Mathematical Sciences to enable students to improve their job marketability after graduation. Considering AIS615 is an accounting subject, students who are not majoring in accounting will find it challenging because it is not their main course, which could result in a conflicting perception. The importance of the student's perception of the course has been proven to impact student achievement significantly. It also offers essential information for educators to use in enhancing future learning approaches. Thus, the aims of this study is to investigates the perceptions of non-accounting students enrolled in an AIS615 course at UiTM Negeri Sembilan, considering that the students are not pure accounting students. The respondents for this study are students enrolled in the AIS615 course, which includes students in Parts 3, 4, 5, and 6. The data for this study is collected using an online questionnaire. In this study, the perception of the AIS course was measured using three components: interest, usefulness, and challenge. The results show that students thought the AIS615 course was interesting, useful, and challenging. It demonstrates that students are willing to take on the challenges of a course that is both interesting and useful in the future.